OPTIMASI PRODUKSI SUMUR EC-6 DENGAN MEMBANDINGKAN PENGANGKATAN BUATAN GAS LIFT DAN ELECTRIC SUBMERSIBLE PUMP - Jonathan Jonathan; Sisworini Sisworini; Samsol Samsol; Hari Oetomo (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
In the world of oil is very common in the production system. This production system produces oil from wells after drilling and well compressions. Over time, the production of a well may decrease due to several parameters of pressure drop and the presence of clay which makes the pipe diameter narrower. There are several methods used to increase the decrease in production including adding artificial lifts such as sucker rod pump, electric submersible pump and gas lift, reservoir stimulation and pipe cleaning if the pipe diameter is reduced due to clay. The well has been installed an artificial lift is a gas lift and this well need an optimization to increase its production. The EC-6 well optimization is planned by comparing the lift-up scenario of the gas lift by adjusting the rate of gas injection and deepening the orifice injection and also an installation of electrical submersible pump. Best percentage of optimization production from EC-6 Well, last scenario is chosen which is new installation artificial lift ESP from gas lift (existing) and gaining 18.52% form existing production